Some Technological Aspects of Adaptive Control of CNC Machine Tools - Tran, Văn Khiêm; Dao, Văn Hiệp (Journal of Technical Education Science, 2008)
This article presents the changes occurred during the process of metal cutting, their effects and influence of cutting force on the processing quality as well as technological system. In the article, the diagrams, by which the processes are controlled, are proposed and analyzed in order to find out the advantages and disadvantages of traditional CNC (Computer Numerical Control). The article also focuses on analyzing all technological aspects of the Adaptive Control (AC) to conclude that the AC is logical development of CNC.